Characterization and Inventory of Ectoparasites in Cultivated Fish at the Aquaculture Technology Development Center (BPTPB) Cangkringan, Sleman, Special Region of Yogyakarta - Ayu Safira; Mahdania Aulia Rahma; Sherly Naswa Salsabila; Subekti Rahayu; Dewi Ambarwati; Mohammad Faizal Ulkhaq (Journal of Fish Health, 2026)
Fish farming has increased significantly compared to capture fisheries due to overfishing and the excessive exploitation of wild fish resources. However, the intensification of aquaculture systems is often followed by the emergence of various diseases, including ectoparasite infestations. Ectoparasites are important pathogens that can reduce fish productivity and health status. Their presence may cause clinical symptoms such as wounds and hemorrhages on the skin and gills, respiratory disorders, abnormal swimming behavior, and even mortality in fish. This study aimed to identify and inventory the types of ectoparasites infesting cultured fish at the Center for Aquaculture Technology Development (BPTPB) Cangkringan, Sleman, Special Region of Yogyakarta, and to determine their prevalence and intensity levels. The research applied a descriptive method through field observations and microscopic examinations, with scraping techniques performed on the skin, fins, and gills of fish. A total of 85 fish samples were examined, consisting of tilapia (n=20), carp (n=21), koi (n=24), and catfish (n=20). The results revealed six ectoparasite taxa infecting cultured fish: Trichodina, Gyrodactylus, Dactylogyrus, Ichthyophthirius multifiliis, Myxobolus, and Epistylis. Among these, Trichodina showed the highest prevalence and intensity, reaching 100% prevalence with an intensity of 840.5 parasite individuals per fish. In contrast, the lowest values were recorded for Gyrodactylus, with a prevalence of 4.76% and an intensity of 1 parasite individual per fish. These findings indicate the need for effective fish health management and parasite control strategies to prevent infections that may reduce aquaculture productivity.